Kadar Silika (SiO2) terhadap Kelimpahan Diatom Bentik di Sungai Jamblang Kabupaten Cirebon - Maharani Zahiratun Haque; Norma Afiati; Oktavianto Eko Jati (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Jamblang River is a concern because it has a very turbid water color due to natural stone mining activities processed by the natural stone industry. One of the natural stones produced at the location of the Jamblang river is andesite rock which has a constituent component is silica. Silica is the second most abundant element in the Earth's crust after oxygen. Silica usually comes from minerals and rocks that dissolve in water. In fresh water, quartz silica is less soluble than amorphous silica. Enrichment of nutrients with silica favors the growth of diatoms, since diatoms need silica for cell wall biogenesis. The amount of silica present in water is not immediately absorbed by diatoms. The sampling method used is the purposive sampling method. The sampling locations set are 4 locations. The most interesting location is location 2 because there are 38 natural stone industries scattered around the location. There is also a simple linear regression statistical test on SPSS which shows the influence of silica levels on the abundance of benthic diatoms in the Jamblang river. The value of Sig. 0.000 shows that there is an influence of silica on plankton abundance in water because the value is < 0.05. The lowest silica content obtained at location 2 is also supported by the least abundance of diatoms found. The low abundance of diatoms is thought to be caused by high TSS numbers, low observed brightness, and low DO numbers.